DESCRIPTION OF ANXIETY LEVEL AND ATTITUDE IN ADOLESCENT TO THE COVID-19 PANDEMIC : Gambaran Tingkat Kecemasan Dan Sikap Pada Remaja Terhadap Pandemi Covid 19 - Marlin Sutrisna; Elsi Rahmadani; Hanifah (Politeknik Karya Persada Muna, 2022)
Baground: The number of Covid-19 cases worldwide has reached 90 million cases, to be precise it reached 90,054,813 confirmed cases of Covid-19, and as many as 1,945,610 patients who died Method: The design in this research is descriptive. The sample in this study were adolescents who were in the Work Area of the Sidomulyo Health Center, Bengkulu City in 2021. Data were collected using an anxiety questionnaire (Hars Scale) and an Attitude Questionnaire. Data were analyzed using chi-square. Results: The results of the univariate test analysis showed that most of the respondents (59.3%) with moderate anxiety, most of the respondents (53.7%) with negative attitudes towards the Covid-19 pandemic. Conclusions: the COVID-19 pandemic can affect adolescents' anxiety and attitudes. Keywords: Anxiety, attitude